Direct experimental observation of facet‐dependent SERS of Cu2O polyhedra - Lin, Jie (2020)
Semiconductor-based surface enhanced Raman scattering (SERS) has attracted great attention due to its excellent spectral reproducibility, high uniformity, and good anti-interference ability. However, its relatively low SERS sensitivity still hinders its further developments in both performance and applications. Since the SERS is a peculiar surface effect, investigating the facet-dependent SERS activity of semiconductor nanostructures is crucial to boost their SERS signals. Although the semiconductor facet-dependent SERS effect is predicted via numerical calculations, convincing experimental evidence is scarce due to complicated and undefined surface conditions. In this work, three facet-defined ({100}, {110}, and {111} facets) Cu2 O microcrystals (MCs) with clear surface atomic configuration are utilized to investigate the facet-dependent SERS effect. The results from the Kelvin probe force microscopy measurements on single Cu2 O polyhedron, demonstrate that the facet-dependent work function plays a crucial role in the interfacial charge transfer process. Comparing with the {110} and {111} facets, the {100} facet possesses the lowest electronic work function, which enables more efficient interfacial charge transfer. The simulation results further confirm that the {100}-facets can transfer the most electrons from Cu2 O MCs to molecules due to its lowest facet work function, resulting in the largest increment of the molecular polarization.